2022
DOI: 10.1038/s41598-022-13025-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of color changes during stability studies using spectrophotometric chromaticity measurements versus visual examination

Abstract: Stability studies are essential to be able to assign an expiration date to medications. Color variation is one of the organoleptic characteristics of actives substances or medications which can indicate the presence of contaminations, impurities or degradations products. However there is no data available comparing the often used visual examination with spectrophotometric measurements during stability studies. The aim of this study was therefore to evaluate precisely how different the two methods are, by compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…After one month of UVA irradiation and concomitant AA2G application, perceptible differences were observed in skin color of guinea pigs (Figure 6B), with ΔE*ab greater than 3.3 except for G1 (Figure 6C). [ 45 ] Skin darkening mainly affected L* values, with no significant effect on a* and b* values (Figure 6C). From the L* values, the skin pigmentation rate was significantly reduced after AA2G administration, and AA2G hydrogel (G5, 48.84 ± 1.28) was significantly better than AA2G solution (G3, 48.06 ± 0.51), while the liposome‐hydrogel system (G6, 51.56 ± 0.95) further enhanced the whitening efficacy thanks to the high skin permeability of liposomes (Figure 6C).…”
Section: Resultsmentioning
confidence: 99%
“…After one month of UVA irradiation and concomitant AA2G application, perceptible differences were observed in skin color of guinea pigs (Figure 6B), with ΔE*ab greater than 3.3 except for G1 (Figure 6C). [ 45 ] Skin darkening mainly affected L* values, with no significant effect on a* and b* values (Figure 6C). From the L* values, the skin pigmentation rate was significantly reduced after AA2G administration, and AA2G hydrogel (G5, 48.84 ± 1.28) was significantly better than AA2G solution (G3, 48.06 ± 0.51), while the liposome‐hydrogel system (G6, 51.56 ± 0.95) further enhanced the whitening efficacy thanks to the high skin permeability of liposomes (Figure 6C).…”
Section: Resultsmentioning
confidence: 99%
“…CBXs were first evaluated for stability in the buffer solution pH 7.4 at 37 °C using a high-throughput UV–vis-based assay, where we followed the changes in the absorption spectra of the compounds for 4 h (Figure ). , To achieve high throughput, the assay was performed in UV-transparent 96-well microplates, and the analysis was automated using a Python script (available at ). First, we determined the most responsive wavelengths for each compound and calculated the absolute difference in absorbance between the first time point and after 4 h. The absolute difference in absorbance was then divided by the absorbance at the first time point to obtain the relative difference in absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…The threshold values used to interpret results to determine visual acceptability and perceptibility as described by Paravina et al were: ∆E00 ≤ 0.8 indicates clinically unnoticeable, 0.8 < ∆E00 ≤ 1.8 is clinically acceptable, 1.8 < ∆E00 ≤ 3.6 considering moderately unacceptable, and 3.6 < ∆E00 ≤ 5.4 is obviously unacceptable, ∆E00 > 5.4 severely unacceptable [33]. Various studies have observed that ∆E values between 1 and 3 seem to be detectable to the human eye, while ∆E levels greater than 3.3 are clinically significant [6,34].…”
Section: Calculation Of the Color Differencementioning
confidence: 99%